Visual Hygiene - An Under-Used Concept in Optometric Care. - Laudon, Richard (Optometry & Visual Performance, 2020)
Visual hygiene should be an essential part of our overall treatment plan. As our visual demands and activities have become more near-oriented, our visual systems have had to make appropriate adaptations. A personalized visual hygiene list will help our patients take a more active role in the management of their eyes and their visual functioning.